Master–slave real-time control strategy in Cartesian space for a novel surgical robot for minimally invasive surgery. (16th December 2016) - Pan, Bo; Qu, Xiaofeng; Ai, Yue; Fu, Yili; Liu, Chang
Abstract: Robot-assisted systems can enhance the precision of surgical procedures, and have been widely used in minimally invasive surgery (MIS). This paper proposes the master–slave real-time control strategy for a novel surgical robot for MIS. The robot is equipped with two instrument manipulators and one laparoscope manipulator. The control strategy solves problems of kinematics transformation on consistency principle, intra-operative re-mapping and tremor attenuation in real-time. The kinematics model of slave instrument manipulators is established, and the master–slave control method in Cartesian space is proposed. Intra-operative re-mapping and real-time tremor attenuation algorithms are also proposed as auxiliary functions to improve surgical robot's performance. The proposed methods are verified by respective experiments. Finally, animal experiment is performed to verify the correctness and efficiency of the control strategy in this research.